2019
DOI: 10.1038/s41467-019-12880-5
|View full text |Cite
|
Sign up to set email alerts
|

Neratinib protects pancreatic beta cells in diabetes

Abstract: The loss of functional insulin-producing β-cells is a hallmark of diabetes. Mammalian sterile 20-like kinase 1 (MST1) is a key regulator of pancreatic β-cell death and dysfunction; its deficiency restores functional β-cells and normoglycemia. The identification of MST1 inhibitors represents a promising approach for a β-cell-protective diabetes therapy. Here, we identify neratinib, an FDA-approved drug targeting HER2/EGFR dual kinases, as a potent MST1 inhibitor, which improves β-cell survival under multiple di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 62 publications
(84 reference statements)
1
86
0
Order By: Relevance
“…A study using another inhibitor of MST1, Neratinib—which also showed MST1 inhibition to be protective—was also performed using STZ-induced diabetes mellitus [ 17 ]. Our data were consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study using another inhibitor of MST1, Neratinib—which also showed MST1 inhibition to be protective—was also performed using STZ-induced diabetes mellitus [ 17 ]. Our data were consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…MST1 induces β cell death and impairs insulin secretion by initiating proteasomal degradation of pancreatic and duodenal homeobox 1 (PDX1), and β cell transcription factor [ 16 ]. In keeping with this finding, genetic inhibition of MST1 protected against β cell apoptosis and improved the diabetic phenotype in streptozotocin (STZ)-induced diabetes model in mice [ 17 ]. This finding prompted a notion that MST1 could be a novel therapeutic target for DM.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The discovery of novel agents that may block β-cell apoptosis and at the same time restore β-cell function is of great importance to fight diabetes. Ardestani et al recently demonstrated that neratinib (Figure 7), an FDA-approved drug targeting HER2/EGFR dual kinases, is a potent mammalian sterile 20-like kinase 1 (MST1) inhibitor, which improves β-cell survival under multiple diabetogenic conditions in human islets and INS-1E cells [48]. Five years ago, it was reported that MST1 is a key regulator of pancreatic β-cell death and dysfunction [49].…”
Section: Highlighted By George Kokotosmentioning
confidence: 99%
“…20-like kinase 1 (MST1) inhibitor, which improves β-cell survival under multiple diabetogenic conditions in human islets and INS-1E cells [48]. Five years ago, it was reported that MST1 is a key regulator of pancreatic β-cell death and dysfunction [49].…”
Section: Highlighted By George Kokotosmentioning
confidence: 99%